Economic Valuation of Bubohu Religious Tourism Village in Gorontalo District - Katili, Annisa Pratiwi; Suman, Agus; Syafitri, Wildan (Journal of International Conference Proceedings, 2023)
The development of industrial tourism at local level directly opens up employment in tourism areas which can be managed and utilised by local communities. Bubohu religious tourism village is one of the tourism villages having a good potential economy, however there still are identified poverty issues in the village. This research calculates the value of potential economic and multiplier effect value of religious tourism village Bubohu by identifying the amount of visitor expenditure, business unit income, expenditure of business units and labour expenditure in this village. The research results obtained the average value of Willingness to pay (WTP) indicating the expenditure of individual tourists visiting amounted to Rp. Rp.395.555 -/person. Then the estimated economic valuation of Bubohu religious tourism village which is based on tourist expenditure amoundted Rp.7.512.391.111. Furthermore, economic value will increase along with tourists coming to visit Bubohu religious tourism. The multiplier effect analysis results acquired that Keynesian Income Multiplier value is 1,25, and Ratio Income Multiplier type 1 is 1,45 as well as Ratio Income Multiplier type 2 is 1,87. The results indicated that the existing tourism activities at Bubohu religious tourism village have a good economic impact on the local communities.